The influence of titanate coupling agent on the performance of barium titanate/PMMA denture base nanocomposites after SBF storage - Elshereksi, Nidal Wanis; Muchtar, Andanastuti; Azhari, Che Husna (Sage Publications Ltd, 2024)
Indexed by WOS